Boosted Heterogeneous Catalysis by Surface‐Accumulated Excess Electrons of Non‐Oxidized Bare Copper Nanoparticles on Electride Support. Issue 2 (17th November 2022) - Han, Sung Su; Thacharon, Athira; Kim, Jun; Chung, Kyungwha; Liu, Xinghui; Jang, Woo‐Sung; Jetybayeva, Albina; Hong, Seungbum; Lee, Kyu Hyoung; Kim, Young‐Min; Cho, Eun Jin; Kim, Sung Wng
Abstract: Engineering active sites of metal nanoparticle‐based heterogeneous catalysts is one of the most prerequisite approaches for the efficient production of chemicals, but the limited active sites and undesired oxidation on the metal nanoparticles still remain as key challenges. Here, it is reported that the negatively charged surface of copper nanoparticles on the 2D [Ca2 N] + ∙e − electride provides the unrestricted active sites for catalytic selective sulfenylation of indoles and azaindoles with diaryl disulfides. Substantial electron transfer from the electride support to copper nanoparticles via electronic metal–support interactions results in the accumulation of excess electrons at the surface of copper nanoparticles. Moreover, the surface‐accumulated excess electrons prohibit the oxidation of copper nanoparticle, thereby maintaining the metallic surface in a negatively charged state and activating both (aza)indoles and disulfides under mild conditions in the absence of any further additives. This study defines the role of excess electrons on the nanoparticle‐based heterogeneous catalyst that can be rationalized in versatile systems. Abstract : A combination of copper nanoparticle and exotic electride support provides novel heterogenous catalysts for selective sulfenylation of (aza)indoles with diaryl disulfides under mild conditions in the absence of any additives. Surface‐accumulated excess electrons of the negatively charged copper nanoparticles anchored on dicalcium nitride, [Ca2 N] + ∙e − electride are responsible for the catalytic reaction that has not been accomplished with typical copper nanoparticles.